FRI0123 Clinical Outcomes Associated with Switching or Discontinuation of Anti-TNF Inhibitors for Non-Medical Reasons. (9th June 2015) - Lebwohl, M.; Skup, M.; Yang, H.; Faust, E.; Kageleiry, A.; Chao, J.; Wolf, D.
Abstract : Background: Anti-tumor necrosis factor (anti-TNF) agents are an important treatment option for Crohn's disease (CD), ulcerative colitis (UC), rheumatoid arthritis (RA), ankylosing spondylitis (AS), psoriasis (Ps), and psoriatic arthritis (PsA). However, patients with a stable response to anti-TNF therapy may discontinue or switch treatments for non-medical reasons such as cost reduction. Objectives: We evaluated real-world clinical outcomes associated with non-medical switching of anti-TNF therapies in the US. Methods: An online, physician-administered chart review collected data on patients with a diagnosis of CD, UC, RA, AS, Ps, or PsA who had response for ≥6-months to an anti-TNF therapy. Physicians, sampled equally across rheumatologists, dermatologists, and gastroenterologists, selected 2 cohorts that were matched on primary diagnosis: patients who discontinued or switched from the anti-TNF on which they achieved response for non-medical reasons (switchers/discontinuers), and patients who did not discontinue for non-medical reasons (continuers). Switchers/discontinuers were followed for 12 months from the date of discontinuation (index date); continuers were followed for 12 months from the date of an office visit within 2 months of the matched switcher/discontinuer's index date. Generalized linear models were used to compare disease flares, disease control, and use of medical services between cohorts with adjustment for baseline demographics, comorbidities, and resource use. Results: 377 matched pairs of switcher/discontinuers and continuers were analyzed (N=754). Compared to continuers, switchers/discontinuers had a higher risk of flares and more frequent flares across all severity levels (Table 1 ). Only 47% of switchers/discontinuers had well-controlled disease symptoms as per the physician, a rate significantly lower (adjusted odds ratio =0.11, P <0.001) than continuers (88%). Switchers/discontinuers had an increased risk of ≥1 inpatient stays ( P <0.01) or emergency department visits ( P <0.01) and had more frequent visits to hospitals, emergency departments, and outpatient clinics (Table 2 ). Conclusions: Switching or discontinuation of an anti-TNF therapy for non-medical reasons was associated with significantly worse clinical outcomes and increased healthcare resource use. Acknowledgements: Design, study conduct, and financial support for the study were provided by AbbVie Inc. AbbVie participated in the interpretation of data, review, and approval of the abstract; all authors contributed to the development of the publication and maintained control over the final content. Medical writing support was provided by Cathryn M. Carter and Tonya Goodman, of Arbor Communications, Inc; this support was funded by AbbVie. Disclosure of Interest: M. Lebwohl Consultant for: AbGenomics, Amgen Canfite Biopharma, Coronado Biosciences, Dermipsor, Lilly, Forward Pharma, Janssen Biotech, LEO Pharmaceuticals, Meda, Merck, Novartis, Pfizer, Taro and UCB Pharma, M. Skup Shareholder of: AbbVie, Employee of: AbbVie, H. Yang Employee of: Analysis Group, which received payment from AbbVie to participate in this research, E. Faust Employee of: Analysis Group, which received payment from AbbVie to participate in this research, A. Kageleiry Employee of: Analysis Group, which received payment from AbbVie to participate in this research, J. Chao Shareholder of: AbbVie, Employee of: AbbVie, D. Wolf Grant/research support from: AbbVie, Consultant for: AbbVie, Speakers bureau: AbbVie